Enhancing the efficiency of the cultivation of cladocerans (Moina sp. and Diaphanosoma sp.) through dietary diversification strategies - Sadia Momota Hena; Abdul Mozid Akanda; Jinnath Rehana Ritu; Mohammad Ariful Islam Sumon; Md Mahfuzul Haque; Saleha Khan (Heliyon)
The establishment of a feeding regimen for cladocerans is crucial in contemporary aquaculture due to their significance as nutrient-rich live feeds for various aquatic species. Three experiments were conducted to optimize the growth and reproduction rates of cladocerans (Moina sp. and Diaphanosoma sp.) using various stocking densities, types of food, and feeding regimens, emphasizing the importance of Haematococcus sp. in enhancing aquaculture productivity. In the first experiment, five different initial stocking densities: 1 × 103 indv. L−1 (T1), 3 × 103 indv. L−1 (T2), 6 × 103 indv. L−1 (T3), 9 × 103 indv. L−1 (T4), and 12 × 103 indv. L−1 (T5) of cladocerans were tested over a 10-day culture period, where T3 demonstrated the best growth. Using the best initial stocking density from experiment 1, the second experiment assessed varying concentrations of Haematococcus sp.: 1 × 105, 5 × 105, 10 × 105, 15 × 105, and 20 × 105 cells mL−1 in T1, T2, T3, T4 and T5, respectively as feed of cladocerans; among them, T3 exhibited the highest population density. Experiment 3 evaluated the effects of three different diets including live Haematococcus sp. (T1), baker's yeast (Saccharomyces cerevisiae) (T2), and Haematococcus sp. + baker's yeast (Saccharomyces cerevisiae) (T3) on the growth of cladocerans over 10 days. The study employed the optimal initial stocking density of cladocerans and the feeding concentration of Haematococcus sp. as determined from the prior two experiments. Notably, T3 yielded the highest zooplankton density in this investigation. These findings indicate that elevating the initial stocking density of cladocerans and increasing the concentrations of Haematococcus sp. as feed up to an optimal level can effectively enhance the population growth of cladocerans. Both very low and excessively high initial stocking density, as well as suboptimal and excessively high concentrations of Haematococcus sp., negatively impact the growth of cladocerans. Moreover, using Haematococcus sp. alone or in combination with baker's yeast (Saccharomyces cerevisiae) enhances the growth and reproduction rates of cladocerans, indicating potential benefits for aquaculture systems.